Perbedaan Kadar Bilirubin Total Dengan Paparan Cahaya Yang Segera Diperiksa dan Ditunda Selama 3 jam - Made Gita Candra Dewi; Ni Luh Putu Devhy; Putu Ayu Parwati (Journal of Medical Laboratory Research, 2025)
Total bilirubin examination serves to determine liver and bile duct function. Pathological hyperbilirubinemia can cause central nervous system disorders to death. Due to the importance of bilirubin results for supporting diagnosis, examinations must follow procedures. However, in the field, there are often issues like lack of control, damaged equipment, and others, resulting in delayed specimens. This study aims to determine the difference in total bilirubin levels with light exposure examined immediately and delayed for 3 hours. This experimental research used 36 sample units from 18 samples with 2 treatment groups: serum exposed to light examined immediately and serum exposed to light delayed for 3 hours. Sampling technique: accidental sampling. Data analysis used the Wilcoxon test. The results showed an average total bilirubin level of 3.1444 mg/dL for immediate examination and 3.1044 mg/dL for delayed examination. The data analysis result p-value 0.000, indicates a significant difference in total bilirubin levels between immediate and delayed examination. This difference occurs due to external and internal factors. External factors include light exposure, storage time, and inappropriate storage temperature. The blue light in lamps can affect the results, leading to a decrease in total bilirubin levels.